Deposit insurance and risk-taking behavior in the credit union industry - Karels, Gordon V; McClatchey, Christine A (Journal of Banking & Finance, 1999)
This paper examines the relationship between deposit insurance and risk-taking behavior within the credit union industry. Time series tests employing industry average financial ratios for federal and state credit unions did not support the increased risk-taking hypothesis. Although federal credit union capital declined immediately following the adoption of deposit insurance, this was most likely the result of reduced capital requirements, not deposit insurance. Liquidity and loan delinquency ratios had a negative time trend coefficient, implying a decline in risk-taking behavior during the post-insurance period. Cross-sectional test results employing Iowa state-chartered credit union data indicated that insured credit unions were better capitalized and more liquid than their uninsured counterparts. Overall there was no evidence that the adoption of deposit insurance increased the risk-taking behavior of credit unions.